2007
DOI: 10.1897/06-493r.1
|View full text |Cite
|
Sign up to set email alerts
|

Fate of atrazine in a grassed phytoremediation system

Abstract: Atrazine is a well-known contaminant of surface waters and has been implicated in point-source pollution at agrochemical dealerships in the Midwest. Although the fate of atrazine has been well documented in soil and water, little is known about the fate of this contaminant and its metabolites within a grassed system. In the present study, [U-ring-14C]atrazine was added to soil in closed systems to determine the fate of the parent compound and its metabolites in soil, including degradation and movement into pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…(1194 ppb to 564 ppb), suggesting that the plant continues to degrade atrazine beyond the metabolite cyanuric acid. These results are consistent with a mass balance study by Henderson et al (2007). In that study, the authors also used 14C atrazine to track degradation and observed production of [ 14 C]CO2, signifying complete mineralization of atrazine.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…(1194 ppb to 564 ppb), suggesting that the plant continues to degrade atrazine beyond the metabolite cyanuric acid. These results are consistent with a mass balance study by Henderson et al (2007). In that study, the authors also used 14C atrazine to track degradation and observed production of [ 14 C]CO2, signifying complete mineralization of atrazine.…”
Section: Discussionsupporting
confidence: 88%
“…The triazine herbicide atrazine has been one of the most widely used herbicides in agriculture for control broadleaf weeds, mainly in corn, sorghum, and sugarcane crops by a reversible inhibition of photosynthesis (Kruger et al 1993;Henderson, Belden, and Coats 2007;Shimabukuro and Swanson 1969). In 2010, 51 million pounds of atrazine were applied across 18 states, with 6.8 million pounds applied in Iowa alone (NASS 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this study tries to determine the presence of hydroxyatrazine, which 81 was not detected in the above study, but has been detected in switchgrass residues in other 82 studies (Henderson et al 2007, Lin et al 2008. 83…”
Section: Introduction 25mentioning
confidence: 91%
“…Stands of switchgrass in 56 combination with other native prairie grasses can reduce atrazine in leachate by 43% as well as 57 promote degradation in the rhizosphere (Belden and Coats 2004). A mass balance study, using a 58 mix of three prairie grasses including switchgrass, showed that atrazine and its metabolites were 59 distributed equally between leaf and root tissue (Henderson et al 2007). More recent research 60 used a microbe-free environment to show that switchgrass is capable of taking up and degrading 61 atrazine into several metabolites (Murphy and Coats 2011).…”
Section: Introduction 25mentioning
confidence: 99%